Average bolometric corrections and optical to X-ray flux measurements as a function of accretion rate for X-ray binaries. Issue 1 (7th April 2022) - Anastasopoulou, K; Zezas, A; Steiner, J F; Reig, P
ABSTRACT: In this paper, we use an RXTE library of spectral models from 10 black hole and 9 pulsar X-ray binaries, as well as model spectra available in the literature from 13 extra-galactic ultra-luminous X-ray sources (ULXs). We compute average bolometric corrections (BC = L band / L bol ) for our sample as a function of different accretion rates. We notice the same behaviour between black hole and pulsar BCs only when ULX pulsars are included. These measurements provide a picture of the energetics of the accretion flow for an X-ray binary based solely on its observed luminosity in a given band. Moreover, it can be a powerful tool in X-ray binary population synthesis models. Furthermore, we calculate the X-ray (2–10 keV) to optical ( V band) flux ratios originating from the disc/corona at different Eddington ratios for the black hole X-ray binaries in our sample. This provides a metric of the maximum contribution of the disc to the optical emission of a binary system and better constraints on its nature (donor type, etc.). We find that the optical to X-ray flux ratio shows very little variation as a function of accretion rate, but testing for different disc geometry scenarios we find that the optical contribution of the disc increases as the p value decreases [ T ( r ) ∼ r − p ]. Moreover, observational data are in agreement with a thicker disc scenario ( p < 0.65), which could also possibly explain the lack of observed high-inclination systems.